The "scar" of a pandemic: Cumulative incidence of COVID‐19 during the first trimester of pregnancy. Issue 1 (13th August 2020) - Cosma, Stefano; Borella, Fulvio; Carosso, Andrea; Sciarrone, Andrea; Cusato, Jessica; Corcione, Silvia; Mengozzi, Giulio; Preti, Mario; Katsaros, Dionyssios; Di Perri, Giovanni; Benedetto, Chiara
Abstract: Congenitally‐ or perinatally‐acquired viral infections can be harmful to the fetus but data are limited about prevalence and outcomes of coronavirus disease 2019 (COVID‐19) disease during the first trimester of pregnancy. We report epidemiologic data from a study investigating a cohort of women who became pregnant just before or during the COVID‐19 pandemic. We recruited 138 consecutive pregnant women attending for first trimester screening (11‐13 weeks of gestation) at Sant'Anna Hospital, Turin, Piedmont, Italy, during the plateau and the falling phase of the COVID‐19 epidemic curve. Patients were tested for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) immunoglobulin M/immunoglobulin G antibody levels and SARS‐CoV‐2 detection in sera and nasopharyngeal swab samples. COVID‐19 cumulative incidence during the first trimester was of 10.1% with high prevalence of asymptomatic patients (42.8%). Similar to the course of the disease in non pregnant adults, 80% to 90% of infections were not severe.The prevalence of reported symptoms was four‐fold higher in SARS‐CoV‐2 positive patients (57%) than in those negative (13%) ( P  < .001), suggesting that direct self‐testing should open doors to confirmatory testing for COVID‐19. Our findings support the need for COVID‐19 screening in early pregnancy in epidemic areas to plan materno‐fetal health surveillance programs. Highlights: 1‐ In a COVID‐19 endemic area, we found a cumulative incidence during the first trimester of pregnancy of 10.1% 2‐ Among positive patients, 42.8% were asymptomatic 3‐ In the COVID‐19 endemic area, a screening test for SARS‐CoV‐2 should be offered to all pregnant women in the first trimester.